How, when, and to what degree do people with alcohol dependence recover their psychological wellbeing and quality of life? The Madrid Recovery Project - Rubio, Gabriel; Esteban Rodríguez, Laura; Sion, Ana; Ramis Vidal, Lilian; Blanco, María J.; Zamora-Bayon, Amelia; Caba-Moreno, Marta; Macias-Molina, Ana I.; Pérez-Sánchez, Dolores; Rubio-Escobar, Enrique; Ruiz-Diez, Joaquín; Marin, Marta; et al. (Frontiers in Psychiatry, 2023)
Introduction: The consensus on recovery from alcohol use disorder (AUD) has shifted towards encompassing psychological well-being and quality of life dimensions. However, few studies have explored the long-term recovery process and its dimensions, timing, styles and modes. The aim of this study is to investigate the extent, timing and process of psychological well-being and quality of life recovery in alcohol use disorder (AUD) patients, as well as the relationship with classic dimensions of AUD recovery. Method: A cross-sectional study has been carried out with 348 participants with AUD, in different abstinence periods (1 month- 28 years), and 171 control subjects. Participants underwent a psychological evaluation, that included self-informed measures of psychological wellbeing, quality of life, negative emotionality and coping strategies related to alcohol consumption avoidance. Statistical analysis included linear and nonlinear regression models between psychological dimensions and maintenance of abstinence; as well as matching the scores of the sample with AUD to those of controls. Scatter plots were used to explore inflection points. In addition, mean comparisons tests were performed between participants with AUD and controls, and by gender. Results: In general, according to the regression models, there were pronounced increases in indices of well-being and coping strategies (and pronounced decreases in negative emotionality) during the first 5 years of abstinence, followed by less pronounced improvements. The matching of AUD subjects in well-being and negative emotionality indices with controls occurs at different times a) 1 year or less: physical health; b) 1-4 years: psychological health; c) 4-10 years: social relationships, well-being and negative emotionality; d) More than 10 years: autonomy and self-acceptance. There are statistically significant differences by gender for the negative emotionality and physical health variables. Conclusions: Recovery from AUD is a long process that involves improvements in well-being and quality of life. Four stages can be described in this process, with the most pronounced changes occurring during the first 5 years of abstinence. However, AUD patients take more time to obtain similar scores to controls in several psychological dimensions.